The Role of Early Child Nutrition in Pulmonary Hypertension-A Narrative Review - Alina-Costina Luca; Cristina Stoica; Cosmin Diaconescu; Elena Țarcă; Solange Tamara Roșu; Lăcrămioara Ionela Butnariu; Bogdan Aurelian Stana; Bogdan Gafton; Antoanela Curici; Eduard Vasile Roșu; Dana Elena Mîndru (MDPI AG, 2024)
Pulmonary hypertension is a complex condition that has distinct characteristics in pediatric populations. This review explores the important role of early childhood nutrition in the growth, progression, and management of pediatric pulmonary hypertension. Nutritional deficiencies, including those of vitamins C, D, and iron, are closely linked to worse outcomes in children with this disease, emphasizing the importance of early intervention to prevent malnutrition and promote growth. Emerging research revealed that promising nutrients like resveratrol, along with modulation of the gut and respiratory microbiomes, may offer therapeutic advances for managing pulmonary hypertension. However, the current literature is limited by a lack of pediatric-specific studies, with much of the data extrapolated from adult populations and animal models, especially rats. This review highlights the need for targeted research to develop effective nutritional interventions aimed at improving outcomes for pediatric patients.